Primitive hydatic cysts of subcutaneous cellular tissue: About 2 observations - Estefan, Alberto; Gomez Fossati, Carlos; Malan, Enzo; V., Avelino Franco (Cirugía del Uruguay, 1974)
Two observations of hydatic cysts of subcutaneous cellular tissue (abdominal wall and gluteal region) are reported. A short revistion of the pathology, clinic and treatment of this unusual hydatic localization is done.